Interferensi Bahasa Melayu Pattani Dalam Berbahasa Indonesia Mahasiswa Thailand Di Universitas Muhammadiyah Surakarta - Kuwing, Miss Aseeyah, Prof.Dr. Markamah,M.Hum, Prof.Dr. Abdul Ngalim,M.M.,M.Hum (2016)
The purpose of this study is twofold. (1) to describe a form of interference in the Malay Pattani language Indonesian language Thai students at the University of Muhammadiyah Surakarta. (2) Describe the factors causing interference in the Malay Pattani language Indonesian language Thai students at the University of Muhammadiyah Surakarta. This type of research is qualitative descriptive. The data source of this research is Thai students at the University of Muhammadiyah Surakarta. Data collected by way refer, records, and interviews. Data were analyzed using methods match the type of translational and methods of contrastive analysis. There are two things that need to be addressed in this study. (1) Existence of interference in the Malay Pattani language Indonesian language Thai students at the University of Muhammadiyah Surakarta namely, (a) Interference phonological elements contained in the phoneme replacement, phoneme deletion, substitution of syllables, and syllables deletion. (b) Interference contained in the lexicon of nouns, verbs, adjectives, pronouns, bookmark, adverbs, prepositions and question words. (c) Interference syntax contained in the type of news sentences, interrogative sentence, and imperative sentences. (2) Factors causing interference in the Malay Pattani language Indonesian language Thai students at the University of Muhammadiyah Surakarta namely, (a) factor is the level of education. (b) Factors kedwibahasawan participants said. (c) social factors in the social environment. (d) factors Indonesian thin user loyalty. (e) Factors not enough vocabulary. (f) factors disappearance of the words that are rarely used. (g) the prestige factor is the source language and style. (h) Factors entrainment habits in the mother tongue. Keywords: interference, Malay Pattani language, Indonesian language